The Asymptotic estimations to efficiency of the algorithm многокритериального choice route in гетерогенной network - Лисовая, И. В. (Problems of Informatization and Control, 2007)
The Considered problem to optimum routing in гетерогенной network by method of the analysis hierarchy Saati. The Relations advantage are founded on result of the measurements, estimation to validity and subjective thoughts about condition of the network. They Are Given comparative estimations to accuracy, stability and asymptotic convergence algorithm searching for of the decision